PERANCANGAN APLIKASI LAYANAN INFORMASI DAN PENGONTROLAN LINGKUNGAN KOMPLEKS PERUMAHAN MENGGUNAKAN METODE PARTICIPANT OBSERVATION - Goenardi, Aditya Argent (TEMATIKA, Journal of Informatics and Information Systems, 2020)
Housing Complex is a residential community that has many houses in one large area. According to Law No. 4 of 1992 concerning housing and settlements, housing is defined as a group of houses that functions as a residential or residential environment that is equipped with facilities and infrastructure. Physically housing is an environment that consists of a collection of residential units which allow social interaction between residents, and is equipped with several social infrastructures, economic, cultural, and services which are subsystems of the city. The Participant Observation Method is a direct observation method used to get supporting data in the place to be studied. which applies the Participant Observation method. Supporting data from the Participant Observation method will be applied in the Housing Complex Information Services Application. The results of this study are an application of information services that can help citizens who need information about housing complexes and control the schedule of waste disposal for cleaning and complex road flow through the portal for security.